Analisis Variasi Radius Deflektor Pada Truck Pick Up Dengan Bak Aerocap Sudut 0° Terhadap Koefisien Hambat Menggunakan CFD - Saputra, Wahyu; Karohika, I Made Gatot; Ghurri, Ainul (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Vehicle shape optimization aims to one of the efforts that can be done at low cost is the addition of deflector-type Drag Reduction Device components that can improve the aerodynamics of Truck Pick Up. Tests were carried out using CFD simulation on 2 variations, namely Truck Pick Up with 0° Aerocap body using 0° radius, 800 radius and 1000 radius deflectors simulated at a speed of 90 km/h using the k-omega turbulence model. Grid independence tests were performed on the determination of the amount of meshing used to minimize errors and optimize iteration time. The simulation results show that the use of Drag Reduction Device type Deflector is able to reduce the drag coefficient and reduce the use of fuel. so that the car is more aerodynamic and increases fuel efficiency. efficiency, with the use of a 1000 radius deflector getting the highest drag coefficient reduction value of 0. and lowering the fuel consumption. coefficient, which is 0.72251111 and reduces fuel consumption by 6.3%, when compared to the deflector radius of 0.000. when compared to the 0 radius deflector. Keywords: Efficiency, Coefficient Drag, Coefficient Pressure, Aerodynamics, Computational Fluid Dynamics